Comparison of driving difficulty between bilateral cataract and non-cataract patients among elderly drivers: a preliminary study - Abd Rahman, Mohd Harimi; Mohd Norizan, Nurul Hafizah; Abdul Mutalib, Haliza; Md Mustafa, Md Muziman Syah (Universiti Kebangsaan Malaysia, 2021)
An age-related ocular disease such as cataract that causes reduction of visual functions would affect the individual driving performance. The aim of this study was to compare driving difficulties between Malaysian drivers with bilateral cataracts and without cataract. This cross-sectional study involved measurement of visual functions [visual acuity (VA) and contrast sensitivity (CS)] and driving difficulty of 61 subjects who are actively driving with valid driving license. Subjects were divided into bilateral cataract group (n=30) and non-cataracts group as control group (n=31); which age and gender matched. Results showed that the mean±SD for composite driving difficulty score in the bilateral cataract group and in the control group were 72.08±15.95 and 87.50±12.60 respectively. It showed that both groups had lower mean composite score which indicates difficulty in driving. Results also showed significant mean difference composite driving difficulty score between cataract and control group (p<0.001). Drivers with bilateral cataracts were also found to have significant difficulty when driving the rain (p=0.034), at night (p=0.013) and when driving on local or highway (p=0.005) compared to drivers without cataract. Subsequent Spearman’s Rho showed significant moderate positive correlation between driving difficulty and binocular CS (rs =0.404, p=0.027). This study showed that drivers with cataract would experience driving difficulties compared to the drivers without cataract.